2020
DOI: 10.1017/s0140525x20000308
|View full text |Cite
|
Sign up to set email alerts
|

Grounded procedures: A proximate mechanism for the psychology of cleansing and other physical actions

Abstract: Experimental work has revealed causal links between physical cleansing and various psychological variables. Empirically, how robust are they? Theoretically, how do they operate? Major prevailing accounts focus on morality or disgust, capturing a subset of cleansing effects, but cannot easily handle cleansing effects in non-moral, non-disgusting contexts. Building on grounded views on cognitive processes and known properties of mental procedures, we propose grounded procedures of separation as a proximate mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 177 publications
3
34
0
Order By: Relevance
“…This invalidation condition was designed to reduce the perceived validity of thoughts and subsequent thought usage. Although this induction was also rather subtle, it was designed in accord with previous research revealing that creating distance from thoughts (either through mindfulness, cleansing, or other means) decreases the use of thoughts (Bernstein et al, 2015;Lee & Schwarz, 2021). Also, research on self-persuasion has demonstrated that physical distance (Briñol et al, 2013), and other forms of separation from one's thoughts, can decrease the use of both positive and negative thoughts affecting self-evaluation (Gascó et al, 2018;Paredes et al, 2019;Santos et al, 2019).…”
Section: Validity Of Thoughtsmentioning
confidence: 99%
“…This invalidation condition was designed to reduce the perceived validity of thoughts and subsequent thought usage. Although this induction was also rather subtle, it was designed in accord with previous research revealing that creating distance from thoughts (either through mindfulness, cleansing, or other means) decreases the use of thoughts (Bernstein et al, 2015;Lee & Schwarz, 2021). Also, research on self-persuasion has demonstrated that physical distance (Briñol et al, 2013), and other forms of separation from one's thoughts, can decrease the use of both positive and negative thoughts affecting self-evaluation (Gascó et al, 2018;Paredes et al, 2019;Santos et al, 2019).…”
Section: Validity Of Thoughtsmentioning
confidence: 99%
“…This standard has not always been met in replication attempts (Ramscar, 2016;Ramscar, Shaoul, & Baayen, 2015). As well, claims of non-replicability have sometimes been based on statistical practices that deviate from best practices (Lee & Schwarz, 2020). Moreover, as noted by Lee, motivated reasoning about research outcomes is not restricted to authors of new research results (Wagenmakers), and is readily found among claims of non-replication.…”
Section: Systematic Examination?mentioning
confidence: 99%
“…• Our target article (Lee & Schwarz, 2021a) • Ropovik, Sparacio, and IJzerman's commentary (Ropovik et al, 2021) • Our "authors' response" to all 27 commentaries (Lee & Schwarz, 2021b) and our response appendix that presents technical details regarding Ropovik et al • Ropovik and IJzerman's blog post • Our present reply to Ropovik and IJzerman's blog post…”
mentioning
confidence: 99%